A PBl approach for acquiring global project experiences in architectural/engineering/construction education - Ibrahim, R. (2007)
A major concern in establishing a global project's operation is ensuring the movement of knowledge amongst the team members for a timeiy and within the budget implementation. Already operating in the complex property development process, a global project team must also work in a situation where professional, cUltural, spatial and technological differences would add the complexity. This paper presents a conceptual framework for an architectural-construction integration (A-CI) design studio curriculum in the context of an architectural graduate program. It aims to apply transdisciplinary principals to educate competent graduates in sustainable global design-build practice.The A-CI curriculum emulates the computerintegrated Project Based Learning laboratory (PBl) model developed at Stanford University, with a focus on the early design phase of a project's design development process. The A-CI curriculum builds on the PBl's framework and principles, extending it to include the project financial and regulatory decision-making process along the planning and architectural design processes that integrate Modular Coordination dimensions for open building systems. C The proposed extended model shares PBl's advantages and costeffectiveness of working collaboratively in a cross-disciplinary environment. The A-CI model will initially build bridges across disciplines by addressing different stakeholders' issues in earlier development life-cycle phases. The paper will first present the literature review, followed by a description on the framework and principles of the PBL model before proposing how we extend the PBl model to integrate the early architectural design phase.